2018
DOI: 10.1080/10503307.2018.1490972
|View full text |Cite
|
Sign up to set email alerts
|

“It’s both a strength and a drawback.” How therapists’ personal qualities are experienced in their professional work

Abstract: The results point to ways in which the personal selves of the therapists may affect their professional role performance. Drawing upon previous research and literature on the topic, the paper discusses how therapists' personal qualities are experienced as affecting their work and suggests several implications for psychotherapy training and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
0
15
0
2
Order By: Relevance
“…Due to the spontaneous quality and moment-to-moment nature of such "mirroring," it is likely that many of these microprocesses take place on an intuitive and implicit level, often outside of the therapist's conscious control. Many therapists report that they experience their listening skills and ability to tune into the experience of others as something that come naturally to them (Bernhardt et al, 2019;Skovholt & Jennings, 2004). However, research on therapist presence has shown that patients rate the sessions as more effective when the therapist had done mindfulness exercises before therapeutic sessions (e.g., Dunn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the spontaneous quality and moment-to-moment nature of such "mirroring," it is likely that many of these microprocesses take place on an intuitive and implicit level, often outside of the therapist's conscious control. Many therapists report that they experience their listening skills and ability to tune into the experience of others as something that come naturally to them (Bernhardt et al, 2019;Skovholt & Jennings, 2004). However, research on therapist presence has shown that patients rate the sessions as more effective when the therapist had done mindfulness exercises before therapeutic sessions (e.g., Dunn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the current case was based on our conception that it would be able to provide both depth and fresh perspectives to central themes and patterns in the larger dataset (Bernhardt et al, 2019) and on our aim of understanding how the therapist's personal way of being might contribute to the shaping of an actual therapeutic change process. In addition, this particular therapist's use of his bodily, nonverbal presence in his therapeutic work, as described to us, distinguished him from the other therapists in the research project and in Psychotherapy Research 3 our view made this case particularly interesting to explore further.…”
Section: Selection Of the Case From The Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Heinonen and Orlinsky (; p. 727) observed that therapists "… experienced themselves as more intensively nurturing and protective in their close personal relationships, but also as more authoritative, critical and demanding , and rather less accepting or tolerant than when with clients" … reflecting "the not unsurprising fact that therapists are more self‐centered and less altruistic in that intimate private sphere of life … where people typically seek satisfaction for their emotional needs." Another reflection of this divergence was described by Bernhardt, Nissen‐Lie, Moltu, McLeod, and Rabu (; p. 6) as a "… tension between perceiving oneself as a helper while dealing with one's own needs for attention and care." Some boundaries are wise to preserve, as noted one senior therapist”: I hope some psychologists are not themselves with clients, because their selves are not therapeutic.…”
Section: Discussionmentioning
confidence: 99%